A comprehensive investigation of halogenated plasmas: from mechanistic studies to applications - Martin, Ina Taylor, author; Fisher, Ellen R., advisor (Colorado State University. Libraries, 2005)
Octafluoropropane (C3F8) and octafluorocyclobutane (C4F8) plasmas were used to deposit thin fluorocarbon (FC) films on Si substrates. The effects of applied rf power (P), substrate position and pulsing the plasma on film composition and thickness were studied. Plasma parameters that limited ion bombardment of the substrate during film deposition, such as pulsing the plasma, and placing the substrate downstream from the source, resulted in more F rich, less crosslinked materials. After developing the FC deposition systems, a C3F8 plasma treatment was chosen to modify polymer microfluidic devices, with the intent of coating the device with a non-ionizable film to reduce the electroosmotic flow (EOF). Acrylic acid (AA) plasmas were also used to treat the microfluidic devices. Both treatments resulted in modified EOF flow values compared to untreated devices. Plasma treated substrates were analyzed using FTIR, X-ray photoelectron spectroscopy (XPS), scanning Auger microcopy (SAM), scanning electron microscopy (SEM), and ellipsometry. Gas-phase studies were performed using laser-induced fluorescence (LIF) and mass spectrometry with energy analysis capabilities. Gas-surface interaction studies of CF2 molecules in these FC systems were performed using our imaging of radicals interacting with surfaces (IRIS) technique, with an emphasis on ion effects. High scattering coefficients (S > 1) indicate CF2 molecules are generated at the surface. Ions were found to contribute to the surface production of CF2 during FC plasma treatment of Si. Specifically, a linear correlation exists between CF2 surface production and the mean energy of ions produced in the plasma. There is also a linear correlation present between S (CF2) values measured and the degree of crosslinking in the deposited FC materials. Additionally, relative density measurements and rotational temperature studies of CF are discussed. This dissertation also summarizes preliminary work involving tetrachlorosilane (SiCl4) plasmas, including gas-phase and SiCl2 gas-surface interaction data collected for SiCl4 and SiCl4/H2 plasma systems. Initial IRIS investigations of SiCl2 molecules during SiCl4 plasma processing of Si demonstrate that there is significant SiCl2 surface production in the parameter range studied. Higher values correspond to systems where etching is the dominant process.
Keywords: analytical chemistry; chemistry; fluid dynamics; gases; physical chemistry; plasma physics